2022
DOI: 10.3390/ijms23158152
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Characterization of a Mice Genetic Model of Absolute Blindness

Abstract: Recent technological development requires new approaches to address the problem of blindness. Such approaches need to be able to ensure that no cells with photosensitive capability remain in the retina. The presented model, Opn4−/− × Pde6brd10/rd10 (O×Rd) double mutant murine, is a combination of a mutation in the Pde6b gene (photoreceptor degeneration) together with a deletion of the Opn4 gene (responsible for the expression of melanopsin in the intrinsically photosensitive retinal ganglion cells). This model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…This test measures the visual acuity of the animals by observing the movement of the animal’s eyes/head following the direction of rotation of the grating stimuli [ 40 ]. The spatial frequency, direction, and contrast of the stimuli were varied to determine visual acuity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This test measures the visual acuity of the animals by observing the movement of the animal’s eyes/head following the direction of rotation of the grating stimuli [ 40 ]. The spatial frequency, direction, and contrast of the stimuli were varied to determine visual acuity.…”
Section: Resultsmentioning
confidence: 99%
“…This test measures the pupillary contraction of the animals to a light stimulus [ 40 ]. It was observed that NaIO 3 injection significantly decreased pupillary contraction, manifesting as a smaller change in the pupillary area to three consecutive stimuli (see Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, wildtype mice tend to stay longer in the dark area since their exploratory behavior toward a new environment is suppressed by the negative stimulus produced by the illuminated area. In the case of rd10 mice, it has been described that the time they remained in the dark chamber was longer, and the rejection of the illuminated compartment increased when light intensity was higher [104]. This aversion to the light of rd10 has been explained by the persistence of photosensitive elements within the degenerative retinas of rd10 mice [104].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rd10 mice, it has been described that the time they remained in the dark chamber was longer, and the rejection of the illuminated compartment increased when light intensity was higher [104]. This aversion to the light of rd10 has been explained by the persistence of photosensitive elements within the degenerative retinas of rd10 mice [104]. PIC-OCTtreated mice spent more time in the illuminated chamber than untreated ones, who showed rejection of the illuminated compartment, with less access and time spent in the light chamber.…”
Section: Discussionmentioning
confidence: 99%